Sari Nanas Sebagai Strategi dalam Pengendalian Hama Kumbang Tanduk (Oryctes rhinoceros) Pada Tanaman Kelapa Sawit - Bangun, Jhon Hardin; Apriliya, Indah (Universitas Medan Area, 2025)
The horn beetle (Oryctes rhinoceros Linn.) is a major pest that attacks young oil palm plants and causes serious damage to the growth points, thereby inhibiting plant productivity and growth. So far, this pest control is generally carried out chemically using synthetic insecticides such as carbofuran and cypermethrin. Although effective in the short term, the use of pesticides risks causing pest resistance, environmental pollution, and harming non-target organisms. Alternatively, biological control using natural attractants based on pineapple juice is a promising approach. Pineapple contains volatile compounds such as ethyl 4-methyl butanoate, flavonoids, and alkaloids that function as attractants as well as pest life cycle inhibitors. This literature study aims to analyze the effectiveness of pineapple juice in controlling O. rhinoceros based on previous findings. The results of the study show that the use of pineapple juice has ecological and economic advantages, and has the potential to be integrated in the Integrated Pest Control (PHT) strategy. Nevertheless, it is necessary to standardize formulation and evaluate effectiveness in various field conditions to optimize its utilization.